Intervensi Mind Positif Dalam Mengatasi Kecemasan Pre Operasi Amandel : Studi Kasus Di RSUD Banyumas - sabila, arini; Muridan (Sociocouns: Journal of Islamic Guidance and Counseling, 2026)
Preoperative anxiety is a common psychological response experienced by surgical patients and may negatively affect readiness and postoperative recovery. Tonsillectomy is one of the surgical procedures that often causes anxiety, especially in pediatric patients. This study aimed to describe the application of positive mindset intervention in reducing preoperative anxiety in a tonsillectomy patient at RSUD Banyumas. This research employed a qualitative descriptive method with a case study design involving a 12-year-old pediatric patient who experienced preoperative anxiety. Data were collected through interviews, observation, and assessment of anxiety levels using the Hamilton Anxiety Rating Scale (HARS) before and after the intervention. The positive mindset intervention was administered for two days prior to surgery and consisted of therapeutic education, positive affirmation, and positive visualization. The results showed a significant reduction in anxiety levels, indicated by a decrease in HARS scores from severe to mild anxiety. Subjectively and objectively, the patient demonstrated improved emotional calmness, increased mental readiness, and reduced physiological signs of anxiety. In conclusion, positive mindset intervention is effective in reducing preoperative anxiety in tonsillectomy patients and can be considered a non-pharmacological approach in preoperative nursing care, particularly for pediatric patients.